Influence of Virtual Influencer Credibility, AI-Generated Content Quality, Parasocial Interaction and Digital Trust on Purchase Intention (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The increasing use of artificial intelligence in digital marketing has transformed the way consumers interact with brands and make purchasing decisions. Virtual influencers, AI-generated content, and personalized digital experiences have emerged as powerful marketing tools that influence consumer attitudes and behaviors. This study investigates the impact of Virtual Influencer Credibility, AI-Generated Content Quality, Parasocial Interaction, and Digital Trust on consumers’ Purchase Intention. Drawing upon contemporary digital marketing and consumer behavior literature, the study proposes a conceptual framework to examine the relationships among these constructs (Lou & Yuan, 2019; Dwivedi et al., 2023). A quantitative research design was adopted, and primary data were collected from 400 respondents through a structured questionnaire using a five-point Likert scale. SmartPLS 4 was employed to assess the measurement and structural models. The measurement model demonstrated satisfactory reliability and validity, with Cronbach’s Alpha and Composite Reliability values exceeding 0.70 and Average Variance Extracted (AVE) values above 0.50. The structural model results revealed that Virtual Influencer Credibility (β =0.288, p < 0.001), AI-Generated Content Quality (β = 0.451, p < 0.001), Parasocial Interaction (β = 0.253, p < 0.001), and Digital Trust (β = 0.526, p < 0.001) have significant positive effects on Purchase Intention. The model explained 57.10% of the variance in Purchase Intention (R² = 0.571), indicating moderate predictive power. The findings suggest that consumers are more likely to develop purchase intentions when they perceive virtual influencers as credible, AI-generated content as valuable, and digital platforms as trustworthy. The study contributes to the growing body of knowledge on AI-driven marketing and provides practical implications for marketers seeking to enhance consumer engagement and purchase behavior through emerging digital technologies.